The Key to Success in Implementing College E-Learning Systems During the Covid 19 Pandemic - Mahargiono, Pontjo Bambang; Laily, Nur; Djuraidi, Achmad (Budapest International Research and Critics University, 2021)
During the Covid-19 Pandemic, changing the learning system to be online-based, learning using e-learning, zoom or google meet. The purpose of this study was to determine student satisfaction with the implementation of e-learning in terms of Information Quality (IQ), System Quality (SQ), Service Quality (SEQ), User (U), User Satisfaction (US) and the net benefits (NB) received by students. The population in this study are students at private universities who use eLearning in their learning system. A sample of 353 respondents using certain criteria. Questionnaire as a research instrument by using an online application. Data analysis using SEM PLS. The results showed that Information Quality (IQ), System Quality (SQ), Service Quality (SEQ) had an effect on User (U) and User Satisfaction (US). The findings of this study also show that User (U) and User Satisfaction (US) is capable of moderating between Information Quality (IQ), System Quality (SQ), Service Quality (SEQ) and net benefits (NB) received. The learning system using eLearning is able to transfer the knowledge of lecturers to students.